Ethical Use of AI in Education & Research: Frameworks for Responsible and Inclusive Learning - Prithula Saha Prethwe; Rajib Chandra Das (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
The accelerated advancement of artificial intelligence (AI) has yielded substantial progress in both research and education, yet concurrently introduces complex ethical considerations. This research examines the ethical dimensions associated with deploying AI systems within educational contexts. Furthermore, AI contributes meaningfully to the advancement of education and research about Sustainable Development Goals 4 and 9. Nevertheless, attention must be directed toward the uncertainties engendered by specific apprehensions, including the notion that AI-driven systems might ultimately supplant human educators. The present study draws upon a comprehensive literature review, supplemented by reports and investigations conducted by researchers, institutions, and organizations dedicated to advancing AI and exploring its educational applications, alongside ethical concerns articulated by global experts and bodies. The findings aim to identify and discuss five salient ethical concerns pertaining to AI in education: hallucination, algorithmic bias, plagiarism, privacy, and transparency. The article culminates in a proposed framework designed to address these concerns and facilitate the ethical utilization of artificial intelligence by students and researchers, thereby promoting responsible AI practices within research and educational domains.